THE IMPORTANCE OF LONGITUDINAL DIMENSIONALITY OF THE SKELETON, EXPLOSIVE POWER AND AGILITY IN DISTINGUISHING YOUNG FEMALE VOLLEYBALL PLAYERS OF DIFFERENT SITUATIONAL EFFICIENCY - Zoran Grgantov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
With the aim of determining the significance of differences in longitudinal dimensionality of the skeleton, explosiveness and agility, 24 female volleyball players of ŽOK Sinj of average age of 13,88±0,85 were classified into 2 subsamples of 12 players (those who were selected and those who were not selected for the competing team). By independent samples t-test, significant differences were found between selected and unselected female volleyball players in all variables assessing explosive power, while no significant differences were found between the groups in the agility test. The absence of significant differences in height and standing reach between the two groups of female volleyball players, and the fact that more efficient players were averagely 10 months older, indirectly indicates that not enough attention was paid to longitudinal dimensionality of the skeleton in the selection process. Premature specialization, as well as disregarding physiological maturity when assessing maximum potential of young athletes, is a well known problem in sports practice. Considering the results of the present research, the selection for the competing team might have been conducted with some disregard of the differences in physiological maturity of individual female volleyball players. Further research of this issue on larger subject samples is needed, which will take physiological maturity into consideration, as well as the specificities of specific player roles in volleyball.